Saldo agropecuário brasileiro de 1989 a 2022: Mudança de perfil e cenário global - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study aims to analyze the agricultural contribution to the Brazilian trade balance from 1989 to 2022 and identify the products with a major share in such results. Moreover, it investigates the changes in the products of the Brazilian agricultural trade and discusses outlooks for Brazil's agricultural trade flows in the short future. Even the agricultural goods as a group of products had positive trade results in all evaluated years, from 2008 on the non-agricultural trade had trade deficits and the positive global trade balance of the Brazilian economy was only possible due to the agricultural trade surplus. The following subgroups of products must be highlighted: meat and edible meat offal, other animal-originated products, coffee, tea, mate and spices, oil seeds and oleaginous fruits, meat preparations thereof, sugars and sugar confectionery, preparations of vegetables or fruit, miscellaneous edible preparations, food industries and wastes thereof, tobacco and manufactured, and albuminoidal substances. They had a positive trade balance in all evaluated years. In terms of share's growth through the series, three subgroups of items had expressive increasing of their share in the agricultural trade surplus over the years, that is, oil seeds and oleaginous fruits, meat and edible meat offal, and sugars and sugar confectionery, especially the two first. The study also highlights the main markets and competitors for the Brazilian agricultural exports and potential suppliers in the context of Brazilian imports of food products. Three key factors will require continuous monitoring due to their impacts on the world food supply, that is, the establishment or deepening of trade and investments bilateral agreements, the continuity of the Russia-Ukraine conflict (and its consequences in the global markets of cereals and fertilizers, and the possible greater incidence of plagues and diseases in an environment of increasing climatic instability.
Keywords: F14; Q11; Q17; 330; agricultural trade balance; Brazil; outlooks